The Impact of the Characteristics of the Audit Office in The Level of Professional Specialization of the External Auditor On The Continuity of the Firm A Field Study on Sudanese Audit Offices - Alhassan , Omer (The Arab Journal of Administration, 2018)
This study aims to measure the effect of the characteristics of Audit Office (awareness of client’s activities, the Audit Office reputation, the size of the Audit Office, and the time linked to the customer) on the professional specialization of external audit and judgment on the continuity of the firm. This research is based on field study in Sudanese Audit Offices. The research data were collected and studied with a designed questionnaire. 90 questionnaires were distributed to external auditors, only six of them were not returned. The questionnaire data were analyzed using (SPSS) program. The study hypotheses have been tested through linear regression model. The results indicated a positive effect that is statistically significant for both characteristics of audit Office on the professional specialization level of the external Auditor as well as for both characteristics of audit Office on the continuity of the firm. In addition, the positive effect that is statistically significant for both the professional specialization of external audit on the continuity of the firm. The study recommends increasing the awareness of the importance of the professional specialization of external audit to the legal professional body that oversees the work of Audit Office and establishing obligatory rules.